Internal and External Sources of Knowledge in Manufacturing and Service Enterprises. A Comparative Analysis of European Union Countries - Wyszkowska-Kuna, Joanna (Comparative Economic Research. Central and Eastern Europe, 2020)
Along with the development of economies based on knowledge, the importance of knowledge input in production processes has been increasing. Enterprises may acquire knowledge input by developing their internal knowledge base and/or purchasing knowledge from external entities. Their internal knowledge base may be developed mainly by employing highly qualified specialists and their own research. The aim of the paper is to examine the importance of all these knowledge sources in manufacturing and services enterprises, as well as to compare their changing role with productivity performance in EU countries. It is based on data from the World Input-Output Database, Eurostat, OECD and EU KLEMS. Thanks to the availability of relevant data, the analysed period covers the years 1995–2018. The study demonstrates that knowledge base, developed through both internal and external sources, played a significantly more important role in the EU-15 than in the EU-12, with a tendency to decrease these disparities (most visible with respect to KIBS input). The growing importance of an external knowledge base was more visible and stable in the EU-12 countries. R&D expenditures were an exception. The recent financial crisis heavily affected only external R&D expenditures.